2016
DOI: 10.1002/ep.12328
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on selective catalytic reduction catalysts for NOx emission abatement from municipal solid waste incinerators

Abstract: Incineration is considered to be an effective disposal method for municipal solid wastes (MSW), which is attracting increasing attention due to its great performance in waste reduction. However, one big problem for incineration process is the release of a number of harmful pollutants. Nitrogen oxide (NO x ) is one of the major pollutants in the exhaust of various combustion processes because it is harmful to both environment and human health. For reducing NO x emission from MSW incinerators flue gases, selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Nevertheless, more recent applications to industrial and municipal waste (MW) incinerators pose new issues related to the heterogeneity and variability of the fuel with the consequent release of different pollutants which have to be suitably treated before emission to the atmosphere [3,4]. In addition to SO x , CO, and particulate matter, exhaust gases deriving from the combustion of solid wastes contain large amounts of alkali and alkaline-earth metals (potassium, sodium, calcium, magnesium), phosphorous, and chlorine [4]. All these pollutants must be controlled within the limit values defined by the more and more stringent environmental regulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, more recent applications to industrial and municipal waste (MW) incinerators pose new issues related to the heterogeneity and variability of the fuel with the consequent release of different pollutants which have to be suitably treated before emission to the atmosphere [3,4]. In addition to SO x , CO, and particulate matter, exhaust gases deriving from the combustion of solid wastes contain large amounts of alkali and alkaline-earth metals (potassium, sodium, calcium, magnesium), phosphorous, and chlorine [4]. All these pollutants must be controlled within the limit values defined by the more and more stringent environmental regulations.…”
Section: Introductionmentioning
confidence: 99%
“…Catalysts for the SCR of NOx in exhaust gases from MW incinerator are generally of the same type employed in traditional power plants, namely V 2 O 5 -WO 3 /TiO 2 . Poisoning/deactivation of such catalysts during operation with the exhaust gases from coal-fired plants has been widely investigated, mainly concerning compounds such as SO 2 , mercury, arsenic, alkaline, and alkaline earth oxides [4]. Under conventional operating conditions, the expected catalyst lifetime has been well defined and possible regeneration strategies proposed, as catalysts represent the main cost of the SCR process [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…So far, some excellent review articles have been reported on the development of SCR catalysts which focused on LT catalysts, 26,27 Mn-based catalysts, [10][11][12][13]28 Ce-based catalysts, 14 rare earth-containing catalysts, 29 metal-exchanged zeolite catalysts 30,31 as well as catalysts for the abatement of NO x from diesel engine exhaust 32 and municipal solid waste incinerators. 33 These reviews introduce the development in the partial topic of deNO x catalysts, which mainly concentrate on the structure−performance correlation, the nature of active sites, and reaction mechanisms for the Mn-and Ce-based catalysts or metal-exchanged zeolite catalysts. Currently, Mn/ Ce-based catalysts still suffer some intractable defects such as poor N 2 selectivity of Mn-based catalysts at higher temperatures and easier sulfation of CeO 2 in the presence of SO 2 .…”
mentioning
confidence: 99%
“…The partial or total replacement of Mg 2+ or Al 3+ cations with Zn 2+ , Ni 2+ , Cu 2+ , Co 2+ or Fe 3+ , Cr 3+ , Mn 3+ can afford a wide variety of LDH materials [28][29][30]. LDH-based materials show good performance as photocatalysts for re-newable energy production [23], photoelectrochemical water splitting [31], supercapacitors [32], denitrification [33][34][35], CO2 capture [36,37], etc. based on their unique layered structure, compositional flexibility, and surface defect design.…”
Section: Introductionmentioning
confidence: 99%